Karakteristik Morfologi dan Uji Aktivitas Bakteri Termofilik dari Kawasan Wisata Ie Seuum (Air Panas) - Zuraidah Zuraidah; Dessri Wahyuni; Eka Astuty (Jurnal Ilmu Alam dan Lingkungan, 2020)
Thermophilic bacteria are group of microorganisms that grow on the range of temperature between 450C and 800C. Tourist areas Ie Seuum which is located in Mosque Subdistrict, Aceh Besar Districts is one of the hot springs in Aceh. This research aims to observe the morphological characteristics and enzyme activity assay in producing amylase that are present in Ie Seuum. This research uses qualitative descriptive method for its characteristics and quantitative for the size of clear zone. The results showed that 4 bacterial isolates were found Ie Seuum namely Ka, Kb, Kc and Kd. Bacterial colonies are irregular shaped, filamentous and circular. The edge of colony are grooved, branched and slick. The elevation of colony are only 2 variations, namely flat and arise, with the surface of the colony some rough and shiny. Thermophilic bacterial colors are beige, yellowish, and transparent. Two isolates are able to produce amylase enzymes and formed the clear zones namely isolates Kb and Kc. Clear zone Kb with an average of 11.5 mm and Kc with an average of 9.5 mm at a temperature of incubation 500C for 48 hours.